Insect fat body cell morphology and response to cold stress is modulated by acclimation - Des Marteaux, Lauren E; Štětina, Tomáš; Koštál, Vladimír (The Journal of experimental biology, 2018)
Mechanistic understanding about the nature of cellular cryoinjury and mechanisms by which some animals survive freezing while others do not is currently lacking. Here, we exploited the broadly manipulable freeze tolerance of larval malt flies (Chymomyza costata) to uncover cell and tissue morphological changes associated with freeze mortality. Diapause induction, cold acclimation and dietary proline supplementation generate malt fly variants ranging from weakly to extremely freeze tolerant. Using confocal microscopy and immunostaining of the fat body, Malpighian tubules and anterior midgut, we described tissue and cytoskeletal (F-actin and α-tubulin) morphologies among these variants after exposure to various cold stresses (from chilling at -5°C to extreme freezing at -196°C), and upon recovery from cold exposure. Fat body tissue appeared to be the most susceptible to cryoinjury: freezing caused coalescence of lipid droplets, loss of α-tubulin structure and apparent aggregation of F-actin. A combination of diapause and cold acclimation substantially lowered the temperature at which these morphological disruptions occurred. Larvae that recovered from a freezing challenge repaired F-actin aggregation but not lipid droplet coalescence or α-tubulin structure. Our observations indicate that lipid coalescence and damage to α-tubulin are non-lethal forms of freeze injury, and suggest that repair or removal (rather than protection) of actin proteins is a potential mechanism of acquired freeze tolerance.
Keywords: Fat Body; larva; tukové těleso; Drosophilid; cytoskelet; Freeze tolerance; malpighické trubice; Malpighian Tubules; Acclimatization; Gastrointestinal Tract; Cold Temperature; aklimatizace; gastrointestinální trakt; zvířata; Diapause; Cytoskeleton; Animals; Larva; Chymomyza; Drosophilidae; nízká teplota; Actin